FUNGSI DAN MAKNA KESENIAN BARONGSAI BAGI MASYARAKAT ETNIS CINA SEMARANG - Putro, Bintang Hanggoro (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2009)
Barongsai is a traditional art of Chinese ethnic in Semarang, which comes from China. That art still existsand develop until nowadays although have lot of pressures both from Orde Lama and Orde Baru. Researchstudies were: (1) origin of Barongsai, (2) form of Barongsai art performance, (3) function of Barongsai art,(4) meaning of Barongsai art for Chinese ethnic in Semarang. Applied research method is qualitativemethod. Techniques of data collection are observation, interview, and documentation studies. Techniqueod data analysis are reducing, clarifying, decrypting, concluding, and interpreting all informationselectively. Techniques of checking relevance data were dependability and conformability. Research resultshows that Barongsai is an art comes from China entered Semarang by Chinese merchant. Form ofBarongsai performance are divided into three stages, those are flag play, Barongsai play, and ending.Function of Barongsai art for Chinese ethnic in Semarang are ritual, entertainment, and politic function.Whereas meaning of Barongsai art for Chinese ethnic in Semarang are symbolic meaning and strategymeaning.Kata Kunci : kesenian barongsai, fungsi, makna, masyarakat etnis Cina